Geology of the Laya area and its surroundings, Baturaja Barat sub-district, Ogan Komering Ulu Regency, South Sumatra Province - Purwaningtyas, Vinsensia (Retii, 2024)
The research area is located in the Laya area and its surroundings, West Baturaja sub-district, Ogan Komering Ulu Regency, South Sumatra Province. Physiographically, the research area is included in the Physiography of the Low Hills and Undulating Plains Zone. In the Laya area and its surroundings, the research area is composed of rocks from Tertiary to Quaternary. The purpose of this study is to determine the geological conditions of the research area including stratigraphy, geomorphology, geological structure, geological history and aspects of the environmental geology in the research area. The method used in this study is surface geological mapping, this method includes observation, description and direct measurement in the field in the form of rock outcrop data, geological structure, geomorphology, sources and natural disasters. The Laya area and its surroundings are divided into 3 Geomorphological Units, namely the topographic geomorphological unit of hills and denudational slopes (D2), the geomorphological unit of denudational plains with gentle - undulating morphology (D5) and the river body unit (F1). The Laya area and its surroundings are composed of 5 rock units from old to young, namely the Kikim tuff unit, the Baturaja calcarenite unit, the Gumai carbonate sandstone unit, the Kasai sandstone unit, and sand. The geological structure that developed in this research area is controlled by tectonic activity which is characterized by the presence of fractures and folds in the form of Pusar anticlines, Pusar synclines, and Laya synclines. The Laya area and its surroundings have abundant natural resources and are used as plantations, baths, and mining. However, on the other hand, the research area has the potential for natural disasters, namely landslides or mass movements. Keyword : Laya Area, Sedimentation, Geomorphological Units, Rock Units.